A review of 100 years of syphilis in Austria from 1921 to 2021. - Julia Kasimir; Sylvia Kirchengast (Human Biology and Public Health)
Syphilis, a deadly sexually transmitted infection (STI), lost its terror with the introduction of antibiotics. Recent epidemiological data, however, revealed a reemergence of syphilis in Europe, despite the availability of inexpensive and effective treatments. In Austria, the epidemiological data are incomplete due to limited reporting requirements. Nevertheless, Austrian mass media reported increasing syphilis rates, as documented for other European countries. This study provides an epidemiological overview of syphilis cases in Austria from 1921–2021 and tested the hypothesis that in Austria syphilis rates increase as observed across Europe. Data on syphilis cases from 1921–2019 in Austria were gathered from statistical yearbooks and reports. Additional sex-specific data for 1998–2021 was provided by the Vienna Health Service. Syphilis incidences were highest in the 1920s and declined steadily until 1993. Since then, cases have increased slightly, peaking in 2009 and 2018 at seven cases per 100,000 residents, the highest incidence syphilis rate since 1975. This increase is comparable to that seen in other European countries, consequently this hypothesis was verified. Men living in Vienna were nine times more likely to be infected with syphilis than women of comparable age. The rising syphilis infection rates in Vienna over the last 30 years correspond to those in other Austrian provinces, but also to those in other European countries. From the viewpoint of public health, the introduction of an obligatory reporting system of all diagnosed syphilis cases in Austria is recommended. In addition, regular screenings, treatment, and efforts to reduce discrimination and stigma against sexual minorities may help to prevent rising syphilis rates.